Analysis of Lighting Arrangement in the Film "Buried" (2010) by Director Rodrigo Cortez - Sagaran, Angling; Sayahdikumullah, Dikdik; Muksin, Muksin (ARTCHIVE: Indonesian Journal of Visual Arts and Design, 2024)
This study examines the use of innovative lighting in Rodrigo Cortez's film "Buried," focusing on its impact on narrative storytelling within a single-location setting. The limited lighting arrangement is key to the film's uniqueness, effectively portraying narrative tension and the protagonist's psychological journey in a creative and technical manner. Using a qualitative approach, the research analyzes each shot to identify key lighting transitions and thematic motifs. It dissects the film's visual strategies, particularly how Cortez manipulates light to convey the protagonist's psychological state and the passage of time in a confined space. The study aims to understand the effects of lighting arrangement on the film's visual mood and its implications for contemporary cinematography, as well as the psychological effects of lighting in film on viewers' perception and emotions. It also seeks to enhance the experience of claustrophobia using lighting as a narrative device to complement the tense atmosphere in the film's scenes. The results contribute to a broader discourse on cinematography's role in shaping film narrative structures, especially in creating deep visual narratives without relying on extensive settings or special effects. This analysis provides insights into the effectiveness of minimalist lighting in low-budget film making with high constraints.